An undergraduate Software Engineering practice course: bridging the academia-industry gap - Paiva, Sofia Larissa da Costa; Souza, Adriana Silveira de; Oliveira, Juliano Lopes de; Ramada, Mariana Soller; Luz, Murilo Lopes da (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3516, 2024)
Teaching problem: Software Engineering (SE) practice comprises a set of activities that Software Engineers perform in their typical professional work to produce solutions for needs arising from stakeholders. To learn these activities, the undergraduate student must leave the controlled academic environments that deal with isolated and simplified problems using a single course point of view to reach concrete world working environments, where complex issues must be solved to address the conflicting interests of several stakeholders. Research question: What approaches to undergraduate courses would provide adequate conditions for students to learn SE practice? Situating the case: This paper reports experiences from applying an approach to teaching SE practice in an undergraduate course using a typical industry scenario, where complex SE projects are executed to meet the needs of actual stakeholders. How this case was studied: The reported experience shows the evolution of the proposed course approach after its application on three academic semesters in an undergraduate SE Bachelor’s Degree program in a public university in Brazil. The research material for this report was informally collected over three years of teaching the course, from 2021 to 2023, and indicates that the course approach promotes students’ professional attitudes and technical competencies.